Inshore migration of tropical glass eels (Anguilla spp.) in Lambeso River, Aceh Jaya District, Aceh Province, Indonesia - Zainal A. Muchlisin; Maulidin Maulidin; Abdullah A. Muhammadar; Dedi F. Putra (Aceh Journal of Animal Science, 2016)
The objective of the present study was to evaluate the migration time of glass eels (Anguilla spp.)  in the estuary of  Lambeuso River, Aceh Jaya District, Indonesia. The survey was done in March and June 2015.  The sampling location was determined based on an initial survey during February 2015 by considering the river condition. Based on initial survey there are no glass eels were recorded during noon time, and therefore the sampling was focused at night. The sampling was done four times a month (weekly basis) for three months (12 times in total) using trap nets based on Hijri Calendar. The trap was settled up to opposite direction of tide (seaward) from 18.00 PM to 06.00 AM  and the catches glass eels were monitoring one-hour interval.  A total of 131 glass eels were sampled during the study, where the samples were only caught on first (new month) and fourth week (old month) base on Hijri Calender  during spring tide and  no glass eels were sampled during second and third weeks. It was concluded that the migration time of the glass eels (Anguilla spp.) in Lambeso Rivers is during the dark moon at the new and old month of Hijri Calendar